Modelling the loss of nitrification inhibitor dosed in water distribution systems subject to pipe corrosion - Zhan, Weixi; Arumugam, Sathasivan (Engineers Australia, 2012)
Copper sulphate dosed as a nitrifier inhibitor in water distribution systems has encountered dramatic loss due to iron pipe corrosion. Chosen as the representative of iron corrosion products, ferric hydroxide flocs at low concentration (<2mg/L) bulk water was found capable of removing dissolved copper via adsorption obeying Freundlich isotherm equation. The adsorption rate can be predicted using a modified Pseudo2second order equation. These two adsorption equations enabled the possibility of modelling dissolved copper loss in the field pipeline caused by iron corrosion. With a few reasonable hydraulic assumptions and corrosion patterns made, the established model succeeded in simulating copper loss occurring in the pipeline where copper dosing has been exercised. These findings and the model established shed light on identifying and quantifying the copper loss mechanism in the field and provide modelling tools to improve the nitrifier inhibition strategy for the long term protection of chloramine in the water distribution system.